The influence of deadwood on the carbon dynamics of a near-natural beech forest - a question of soil moisture? - Robin Schäfferling; Eric Zeidler; Alina Azekenova; Gabriela Fontenla-Razzetto; Alexandra Koller; Patrick Wordell-Dietrich; Lilli Zeh; Britt Kniesel; Stefan Julich; Kenton Stutz; Karl-Heinz Feger; Karsten Kalbitz; et al. (2025)
Deadwood is an essential component of intact forest ecosystems. It is a hotspot of biodiversity, can contribute to water retention and has complex effects on various soil functions, such as the quality and quantity of soil organic matter. Whether deadwood makes a positive contribution to carbon storage in forest soils, and how site-specific parameters might contribute, has not been extensively investigated. We therefore ask how the effect of deadwood on the formation and stabilisation of soil organic matter varies with soil moisture.The study was carried out as part of the BENEATH project in a near-natural beech forest in the Dübener Heide near Leipzig, Germany. Three monitoring sites (wet, intermediate, dry) were established on the slope of an old moraine along a natural soil moisture gradient. At all sites, undisturbed soil samples were taken at three depths (0-10 cm, 10-20 cm, 20-30 cm) directly under deadwood in an advanced stage of decay, as well as reference samples (at a distance of 2 m from the deadwood). Soil solution was collected under deadwood and on reference plots using suction plates and cups at 5 cm and 20 cm depth, respectively. Carbon (C) and nitrogen contents were determined for all samples. For soil samples, the size of differently stabilised C pools was determined by density fractionation. Soil respiration was measured monthly by chamber measurement on deadwood-influenced soil and on reference plots. Volumetric soil water content and soil temperature were continuously recorded using SMT100 sensors.The highest soil organic carbon (SOC) contents and the greatest changes due to deadwood were found between 0 and 10 cm depth. At the wet and dry sites, deadwood had a positive effect on SOC content, at the intermediate site the effect was negative. SOC stabilisation was not affected. The concentration of dissolved organic carbon (DOC) in the soil solution was higher under highly decomposed deadwood than at the reference sites. Overall, the highest values were measured on the wet site. Soil respiration was increased on both wet and dry site under the influence of deadwood compared to the reference. The results indicate that the effect of deadwood on C dynamics is critically dependent on soil moisture. The influence of the deadwood itself on the soil water balance seems to be of particular importance. It is likely that changes in soil moisture (due to deadwood or soil properties) will lead to changes in microbial activity with effects on the intensity of processes such as microbial decomposition of SOC or release of organic C from deadwood or litter.Our investigations should contribute to a better understanding of the role of deadwood in the C-cycle of forest soils. They can provide information for a more accurate accounting of C fluxes in forests and for a more climate-smart forest management.